The Analysis of QR Code-Based Books to Develop Cognitive Aspects of 5-6 Year Old Children - Nina Veronica; Sofi Yunianti; Naili Saida; Harun Harun; Arif Rohman (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Appropriate learning media is one of the keys to successful education, especially in early childhood education. This study aims to develop QR code-based books as a means of developing the cognitive abilities of children aged 5-6 years. The research approach uses research and development (RD) with development models that can be carried out in the classroom, one of which is the ADDIE research model (analysis, design, development, implementation, evaluation). Data collection techniques in this study used observation and questionnaires. The results of the expert's assessment showed that the media got a proportion of 79% in the